Experimental Investigation into the Onset of Stall Flutter on Tiltrotor Blades - Croke, A.D.; Zagaglia, D.; Woodgate, M.A.; Green, R.B.; Barakos, G.N. (My University, 2023)
A wind tunnel investigation into the stall of tiltrotor blades in propeller mode was undertaken. A custom blade set was instrumented with fully bridged axial strain gauges to monitor the flap bending strain at two radial locations. Propeller torque data was also analysed. The propeller was tested at varying blade pitch angles, advance ratios and rotational frequencies to clearly identify the blade stall boundary. Stall onset manifested in the strain results as a departure from linear behaviour of the bending strain versus pitch angle curves, an increase in the standard deviation of the strain gauge measurements, the presence of non-harmonic content in the strain spectra and a non consistent oscillation amplitude in the strain time history. For an increasing blade pitch angle, a sudden development of stall was found with variation in RPM as opposed to a more gradual onset as the advance ratio was increased.
Keywords: Aerodynamics